Implementasi Model Project-Based Learning pada Pembelajaran Unsur Gelap Terang dalam Seni Rupa Kelas 6 di SD 2 Karang Malang Kudus Berdasarkan Kurmer - Lu’lu’ul Maknun; Wasis Wijayanto (STKIP Subang, 2025)
Indonesia, as a developing country, greatly needs a creative younger generation to contribute to education, culture, and technology. Creativity can be enhanced through education, particularly in elementary schools through the Cultural Arts and Crafts (SBDP) subject. Learning SBDP is an important aspect of developing students' aesthetic abilities and creativity. This study examines the implementation of teaching light and dark elements in visual arts in grade 6 at SD 2 Karang Malang by applying the Merdeka Curriculum using a Project-Based Learning model, deep learning, and inquiry approaches. The study uses a qualitative descriptive method with data collection through teacher interviews, lesson plan documentation, and observation of student products. Learning media such as projectors, whiteboards, and drawing tools are used to support the learning process. The learning process was carried out by combining theory and practice through direct exploration in the school environment, group discussions, and the application of shading techniques. Students' product outcomes demonstrated their understanding and skills in drawing objects using light and dark techniques that create volume and depth. This learning approach encourages creativity, analytical skills, as well as character development in students in accordance with the Pancasila Student Profile. This article is expected to provide practical references for teachers and related parties in developing innovative, contextual, and meaningful arts and culture learning for elementary school students. Evaluations indicate the success of the methods, media, and approaches used in enhancing students' art skills. However, time planning and facilities need to be improved to make the learning process more optimal.